S100A8 and S100A9 Promote Apoptosis of Chronic Eosinophilic Leukemia Cells - Lee, Ji-Sook; Lee, Na Rae; Kashif, Ayesha; Yang, Seung-Ju; Nam, A. Reum; Song, Ik-Chan; Gong, Soo-Jung; Hong, Min Hwa; Kim, Geunyeong; Seok, Pu Reum; Lee, Myung-Shin; Sung, Kee-Hyung; et al. (Frontiers in Immunology, 2020)
S100A8 and S100A9 function as essential factors in inflammation, and also exert anti-tumor or tumorigenic activity depending on the type of cancer. Chronic eosinophilic leukemia (CEL) is a rare hematological malignancy having elevated levels of eosinophils, and characterized by the presence of the FIP1L1-PDGFRA fusion gene. In this study, we examined the pro-apoptotic mechanisms of S100A8 and S100A9 in FIP1L1-PDGFRα+ eosinophilic cells and hypereosinophilic patient cells. S100A8 and S100A9 induce apoptosis of the FIP1L1-PDGFRα+ EoL-1 cells via TLR4. The surface TLR4 expression increased after exposure to S100A8 and S100A9, although total TLR4 expression decreased. S100A8 and S100A9 suppressed the FIP1L1-PDGFRα-mediated signaling pathway by downregulating FIP1L1-PDGFRα mRNA and protein expression, and triggered cell apoptosis by regulating caspase 9/3 pathway and Bcl family proteins. S100A8 and S100A9 also induced apoptosis of imatinib-resistant EoL-1 cells (EoL-1-IR). S100A8 and S100A9 blocked tumor progression of xenografted EoL-1 and EoL-1-IR cells in NOD-SCID mice, and evoked apoptosis of eosinophils derived from hypereosinophilic syndrome as well as chronic eosinophilic leukemia. These findings may contribute to a progressive understanding of S100A8 and S100A9 in the pathogenic and therapeutic mechanism of hematological malignancy.